1997
DOI: 10.1038/bjc.1997.483
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an antigen homologous to the human CO17-1A/GA733 colon cancer antigen in animal tissues

Abstract: Summary The C01 7-1A/GA733 antigen is associated with human carcinomas and some normal epithelial tissues. This antigen has shown promise as a target in approaches to passive and active immunotherapy of colorectal cancer. The relevance of animal models for studies of immunotherapy targeting this antigen in patients is dependent on the expression of the antigen on normal animal tissues. Immunohistoperoxidase staining with polyclonal rabbit antibodies to the human antigen revealed the human homologue on normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A search for physiological expression of the molecule revealed that it was strongly expressed on epithelial cells (Claas et al, 1996). The same pattern of expression has been described for the panepithelial glycoprotein EGP of the mouse and the human epithelial glycoprotein antigen/major gastrointestinal tumor-associated protein GA733-2/EGP314 (Bergsagel et al, 1992;Momburg et al, 1987;Zaloudik et al, 1997). Since expression of GA733-2/EGP314 is used as diagnostic and therapeutic tool (Fagerberg et al, 1995;Li et al, 1997), it was of interest to evaluate, whether D5.7A is, indeed, the rat ortholog, which would o er a possibility to elaborate functional activities of the molecule.…”
Section: Resultsmentioning
confidence: 55%
“…A search for physiological expression of the molecule revealed that it was strongly expressed on epithelial cells (Claas et al, 1996). The same pattern of expression has been described for the panepithelial glycoprotein EGP of the mouse and the human epithelial glycoprotein antigen/major gastrointestinal tumor-associated protein GA733-2/EGP314 (Bergsagel et al, 1992;Momburg et al, 1987;Zaloudik et al, 1997). Since expression of GA733-2/EGP314 is used as diagnostic and therapeutic tool (Fagerberg et al, 1995;Li et al, 1997), it was of interest to evaluate, whether D5.7A is, indeed, the rat ortholog, which would o er a possibility to elaborate functional activities of the molecule.…”
Section: Resultsmentioning
confidence: 55%
“…VV GA733-2 also prevents growth of syngeneic Ag -positive tumor cells in mice. The high amino acid sequence homology between the mouse and human GA733 Ag in normal tissues, 23 and the similarity in normal tissue distribution 24 makes the mouse a relevant model for experimental active immunotherapy against the GA733 Ag.…”
mentioning
confidence: 99%
“…Moreover, the comparison to control adenovirus-transduced controls rules out any nonspecific effects of adenovirus infection. DC are known to effectively internalize cellular fragments from apoptotic or necrotic cells and process these proteins for presentation by MHC class I and class II molecules (25,35). Should tumor infiltrating DC internalize such fragments from mEGP-expressing tumor cells in vivo, DC presentation of TAA would be expected to be inhibited by the internalized mEGP.…”
Section: Discussionmentioning
confidence: 99%
“…When expressed ectopically in fibroblasts or epithelial cells, GA733-2 has been shown to mediate homotypic cell:cell interactions and to interfere with adhesion mediated by conventional adhesion molecules (23,24), but its physiological function is not known. mEGP bears 81% amino acid identity to GA733-2, has a similar expression profile in normal tissues (19,25), and is similarly overexpressed in some murine tumor cell lines. As part of an effort to establish a murine model for anti-carcinoma immune responses, we attempted to immunize mice with DC-expressing mEGP.…”
mentioning
confidence: 99%